Detergent potential of enzymes of dairy microflora and their effect on the shelf life of milk products - Beena A K (Department of Dairy Science, College of Veterinary and Animal Sciences, 2010)
A study was conducted to assess the detergent potential of a spoilage protease enzyme obtained from the microflora of dairy plant environment. An attempt was also made to study the impact of selected enzyme producers on the shelf life of curd (dahi) and sterilised skim milk. A total of 71 bacterial isolates obtained from dairy environment were screened for their ability to produce spoilage enzymes like proteases lipases and lecithinases. Based on the spoilage potential, Pseudomonas aeruginosa (P12) isolated from pasteurised milk and Bacillus cereus (S4) isolated from sterilized skim milk were selected for further work. The influence of spoilage enzymes on selected physico-chemical characteristics of curd (dahi) and sterilized skim milk was evaluated by preparing the products from milk precultured with isolate P12 and S4. In general, proteolysis of milk was found to have an adverse effect on the quality of products. The stimulatory effect of proteolytic products of P12 and S4 on curd starters was evident from the higher values of acidity, firmness and syneresis in treated curd. The spoilage enzymes adversely affected the overall quality and shelf life of curd. In treated sterilised milk, tyrosine and NPN values were highly elevated. A linear correlation was found to exist between off-flavour and proteolysis. Curd and sterilised skim milk prepared from milk precultured with proteolytic organism were significantly different from that of control. The possibility of exploiting an alkaline protease from spoilage organism in dairy plant sanitation was also looked into. Environmental conditions for the production of alkaline protease by a psychrotrophic strain of Bacillus cereus (S4) was optimised in whey based medium. The protease used in this trial preferred an alkaline medium to remain stable. The enzyme was found to be stable over a wide temperature range of -10°C to 80°C and a pH range of 7.0 to 12.0. The metal ions Ca++, Mg++, Zn++ and Hg++ enhanced the enzyme activity. Lack of inhibition by Hg++ suggested lack of disulphide bonds in the active site of enzyme. Significant inhibition of activity by serine inhibitors indicated an essential serine residue in the active site of enzyme. The deleterious effect of EDTA on enzyme activity showed the supportive role of divalent cations. Marked residual activity on treatment with β-mercaptoethanol indicated the absence of cysteine residue for the enzyme. Enhancement of protease activity in the presence of surfactants and stability in the presence of H2O2 signified its potential to be used as detergent additive. Qualitative assessment of cleaning efficiency of inbuilt formulation substantiated the superiority of enzyme based formulations. Ammonium sulphate fractionation, dialysis and gel filtation using seralose 4B and Seralose 6B were effective in purifying the protease preparation by 141.31 fold. The purified protease was found to be a homogenous preparation of molecular weight of 50.5 kDa as determined by SDS PAGE.